Theory and practice of computation: proceedings of workshop on computation theory and practice (WCTP2015). - Workshop on Computation: Theory and Practice (2015 Cebu City, Philippines); Nishizaki, Shin-ya.; Numao, Masayuki; Caro, Jaime D.L.; Suarez, Merlin Teodosia C.; Libtech/IgLibrary.
This is the proceedings of the Fourth Workshop on Computing: Theory and Practice, WCTP 2015 devoted to theoretical and practical approaches to computation. This workshop was organized by four top universities in Japan and the Philippines: Tokyo Institute of Technology, Osaka University, University of the Philippines - Diliman, and De La Salle University. The proceedings provides a view of the current movement in research in these two countries. The papers included in the proceedings focus on the two research areas: theoretical and practical aspects of computation.
Keywords: Computer science -- Congresses; Information theory -- Congresses